Forensic odontology : principles and practice - David, Thomas J.; Lewis, James M. (Assistant professor of dentistry) (London : Academic Press, an imprint of Elsevier, 2018)
Forensic odontology, principles and practice details the aspects necessary to become an accomplished forensic odontologist, including an illustration of the skills necessary to become an expert witness. The book is ideal for both the experienced and novice forensic odontologist, covering many fields of expertise, including civil and criminal matters. The civil side involves standard of care and personal injury matters, while the criminal side involves not only dental identification, but management of mass fatality incidents, age assessment, child and elder abuse, and bitemark analysis.--
Includes bibliographical references and index.
Keywords: Dental jurisprudence; Dental jurisprudence -- United States